Influence of presumed influence on thinness as a beauty ideal for girls. - Soh, Wai Siong. (2008)
This is a direct response to Park’s (2005) call for further research on the Influence of Presumed Influence (IOPI) paradigm or indirect “two-step flow of mass media communication” which incorporates a “social context” into media effect studies. Data collected from 401 female respondents aged 16 to 19 were used to test six different hypothesized Path Models using path analysis. As opposed to merely revalidating male-female differences (Park, 2005), six IOPI pathways were constructed to examine the plausible role that family (mother) and female peers play in propagating the thin ideal among girls. This study highlights the potential roles that mothers, female peers, educators and policy makers can play to prevent girls from heading towards “dangerous curves” during adolescence. An interesting finding was that a 90.9% majority of normal weight respondents (or 229 respondents) were reportedly dissatisfied with their current physique despite weighing normal. Similarly, a 58.7% majority of underweight respondents (or 78 respondents) expressed dissatisfaction over their thin bodies and desired to lose weight further. A total of three Path Models were partially supported in the study. Path Model II clearly supports Park’s (2005) postulation that a presumed influence on self could occur before a perceived influence on significant others (mother) to result in desire to be thin. Path Models IV and VI validate Park’s (2005) original findings that the presumed influence on significant others (in particular female peers) would precede the perceived influence on self to result in the adoption of weigh losing behaviors. It was interesting that when it comes to the influence on the desire to be thin, we could only see that the “influence of self” has an impact on the desire to be thin. That is, the “influence on self” may have an impact on “influence on significant others or female peers” but the latter will not affect the desire to be thin. On the other hand, if the “influence on significant others or female peers” exerts an impact on “influence on self”, it will result in desire to be thin.